Teaching of programming in advanced course of informatics - Valentina Dagienė; Jonas Blonskis (Lietuvos Matematikos Rinkinys)
Teaching of programming in secondary school raises some problems: how to teach programming, which language and environment to choose, what kinds of tasks to prepare, etc. The paper deals with these questions. The objective and component programming are briefly described as the most suitable for developing programming skills of students. The stages in teaching of programming are analyzed: basic computer skills, basic knowledge in programming, and developing of programs.